The Routledge Handbook of Feminist Bioethics - Rogers, Wendy; Scully, Jackie Leach; Carter, Stacy M.; Entwistle, Vikki A.; Mills, Catherine (ROUTLEDGE HANDBOOKS IN APPLIED ETHICS, 2023)
The Routledge Handbook of Feminist Bioethics is an outstanding resource for anyone with an interest in feminist bioethics, with chapters covering topics from justice and power to the climate crisis. Comprising forty-two chapters by emerging and established scholars, the volume is divided into six parts: I Foundations of feminist bioethics II Identity and identifications III Science, technology and research IV Health and social care V Reproduction and making families VI Widening the scope of feminist bioethics The volume is essential reading for anyone with an interest in bioethics or feminist philosophy, and will prove an invaluable resource for scholars, teachers and advanced students.